Metodološki vidiki preučevanja srbskega ekspresionizma - Stojanović-Pantović, Bojana (Jezik in slovstvo, 2000)
The article highlights the key open problems in research on the expressionist movement in Serbian literature. A discriminative and delicate application of a set of criteria can help us define and describe phenomenon, placing it between the better identified and more extensive aesthetic typology concepts of modernism and avant-gardism. This does not refer only to the explict, programmatic orientation, but also to the poetic, prose and dramatic practice of Serbian expressionists.
Keywords: srbska književnost; ekspresionizem; Expressionism; metodologija